REVIEWING GENDER-BASED VIOLENCE AGAINST WOMEN AND HIV/AIDS AS INTERSECTING ISSUES - Leburu, Goitseone; Phetlho-Thekisho, Nomonde (Social Work/Maatskaplike Werk, 2015)
<span style="font-family: ’Times New Roman’,’serif’; font-size: 14pt; mso-bidi-font-size: 12.0pt; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">Gender-based violence against women continues to be endemic in different forms and in different settings. This form of violence cuts across status, class, religion, race and economic barriers. It occurs at home, in society, in the immediate community, at the work place and in various institutions. This epidemic in most cases also puts women at a greater risk of contracting HIV and Aids. This article reviews gender-based violence and HIV and Aids as intersecting issues. Understanding these phenomena can provide valuable information that could be useful in generating new knowledge within an existing body of knowledge.